Evaluation of Teacher Leadership in the Implementation of Independent Learning Curriculum in Secondary Education Units - Nurainiah; Akyuni, Qurrata; Saputra, Nanda (LPPM Undiksha, 2023)
Base on the reality there are still many teachers who have not changed their way of leadership, the impact is that obstacles and difficulties are often found in implementing the independent curriculum. It is urgent to evaluate teacher leadership because there is a gap between theory, expectations, and reality. The research objective describes teacher leadership in implementing the independent learning curriculum. Literacy and numeracy skills in the curriculum require changes in teacher leadership in implementation.The research method uses Mixed Methods with a convergent (concurrent) parallel design. The research subjects were junior high schools and the objects were teachers. The data collection technique was through a survey with a questionnaire which was developed and given to 70 teachers. Data was also obtained through in-depth interviews with teachers. Quantitative data analysis used SPSS version 26 and qualitative data were analyzed by collecting interview data, reducing and grouping data that intersected one another. The results showed that 54.12% of teachers already had leadership insights and 67.66% agreed to apply leadership in the independent curriculum. Reinforced through the results of interviews that the implementation of an independent curriculum is very urgent to overcome learning loss in producing graduates. Novelty, found from Leadership Insights, the concept of driving teachers provides opportunities for teachers to take part in training and share knowledge massively to accelerate overcoming learning loss in junior high schools.